Problems in diabetes managment in school setting in children and adolescents with type 1 diabetes in Serbia - Ješić Maja D.; Milenković Tatjana; Mitrović Katarina; Todorović Slađana; Zdravković Vera; Ješić Miloš M.; Bošnjović-Tucaković Tatjana; Marković Slavica; Vorgučin Ivana; Stanković Sandra; Sajić Silvija (Vojnosanitetski Pregled)
Background/Aim. Children with type 1 diabetes typically spend one-third of the day in school and they should achieve the same level of diabetes management there as they do outside the school environment. The aim of this study was to identify problems in diabetes management in children with type 1 diabetes at school according to the perceptions reported by children and parents. Methods. This crosssectional survey was carried out at nine public hospitals in Serbia with a cohort of 6-18-year old children/adolescents. The parents were personally informed about the objectives of the survey and the necessity to involve their children. The self-reporting questionnaire included demographic information as well as some questions that helped to evaluate the general situation of children with type 1 diabetes at school. Results. The obtained results show that not all children test blood glucose levels at school (50% of children in the 6-10- year-old age group and 67.3% in the age group over 11 years) and that not all children receive insulin at school (81.1% vs 18.9%, and 57.7% vs 42.3%, respectively). The frequency of severe hypoglycemia was 2.7% in children and 3.3% in adolescents. A high proportion of teachers did not have diabetes training. Conclusion. This brief report about problems in children and adolescents with type 1 diabetes at school in Serbia indicates what happens in the school setting and suggests how to improve control of this disease and facilitate the complete integration of children with diabetes at school.